Perbedaan Efektivitas Edukasi dengan Metode Demonstrasi dan Video Pijat Bayi terhadap Pengetahuan dan Keterampilan Ibu - Mandalin, Bania; Fatimah, Yulia Ulfah; Widiawati, Ida; Suparman, Suparman (LPPM Hang Tuah Pekanbaru, 2024)
In Indonesia, 29.9% of stunting cases are undiagnosed, and this figure increases to 70% worldwide. Babies can benefit from various forms of stimulation, including massage. This study aimed to evaluate the efficacy of video tutorials on infant massage compared to traditional methods in teaching appropriate care to new mothers. This research uses a quasi-experimental design with a quantitative approach. The design uses two treatment groups instead of a control group. In each intervention group, the research sample consisted of 33 mothers whose babies were aged between 1 and 12 months. The sampling process uses probability sampling. To analyze data using univariate methods, we used the Wilcoxon test to determine differences in knowledge and skills and to determine differences in intervention effectiveness, we used the Mann-Whitney test. The mother's level of knowledge before and after the intervention was shown by the results of the Wilcoxon test. The skills acquired as well as the knowledge and skills of the video group showed a p-value of 0.000 < 0.05 after the video intervention. Therefore, in the group that underwent the demonstration, the p-value for knowledge was 0.002 < 0.05 and for skills was 0.000 < 0.05. This means that the results of knowledge and skills in these groups are different. Neither the demonstration method nor the baby massage video method differed significantly in effectiveness in terms of maternal education, according to the Mann-Whitney test (P value = 0.201). The skills test results for both interventions were statistically significant (P = 0.000), indicating that the video education method had a different impact on mothers' skills compared to the demonstration method. The impact of the demonstration is that the mother's knowledge increases and the mother can provide baby massage correctly.